Infliximab and/or immunomodulators inhibit immune responses to trivalent influenza vaccination in adults with inflammatory bowel disease. (1st March 2014) - Hagihara, Yoshie; Ohfuji, Satoko; Watanabe, Kenji; Yamagami, Hirokazu; Fukushima, Wakaba; Maeda, Kazuhiro; Kamata, Noriko; Sogawa, Mitsue; Shiba, Masatsugu; Tanigawa, Tetsuya; Tominaga, Kazunari; Watanabe, Toshio; et al.
Abstract: Background and aims: Appropriate influenza vaccination is important for patients with inflammatory bowel disease under immunosuppressive therapy. The purpose of this study was to evaluate the influence of immunosuppressive therapy on the immune response to the trivalent influenza vaccine in adult patients with inflammatory bowel disease. Methods: In this cohort study, 91 participants received a single dose of influenza vaccine for the 2010/2011 season. Serum samples were collected at 3 different times (pre-vaccination, 3 weeks post-vaccination, and after flu season) to measure hemagglutination inhibition antibody titers. Immune responses were compared based on immunosuppressive therapy. Results: Among the 88 subjects who completed the study, the influenza vaccine induced a more than 4-fold increase in the mean antibody level for all flu strains. The overall seroprotection proportion (post-vaccination titer ≥ 1:40) was 81% for H1N1, 61% for H3N2, and 86% for B. Treatment with an immunomodulator reduced the immune response to the H1N1 strain (OR = 0.20, p = 0.01), and treatment with infliximab reduced the immune response to the other strains (H3N2 strain: OR = 0.37, p = 0.02; B strain: OR = 0.18, p = 0.03). Combination therapy with azathioprine/6-mercaptopurine and infliximab significantly inhibited the immune response to H1N1 (OR = 0.056, p = 0.02). Conclusions: Infliximab and/or immunomodulators inhibit immune responses to some strains of trivalent influenza vaccination in adults with inflammatory bowel disease. For optimization of the trivalent influenza vaccination for patients with adult inflammatory bowel disease treated with immunosuppressive agents, establishing an effective vaccination method is crucial.